Scientist Spotlights: Online assignments to promote inclusion in Ecology and Evolution. Issue 22 (8th October 2020) - Brandt, Samantha; Cotner, Sehoya; Koth, Zoe; McGaugh, Suzanne
Abstract: Scientific disciplines face large diversity challenges, with the fields of ecology and evolution being among the most homogeneous—specifically with respect to race and ethnicity. These problems have been recently compounded by large‐scale racial unrest, highlighting some of the underlying disparities that have led to these diversity challenges, and a global pandemic, which, by moving instruction online, has created new challenges for inclusive teaching. Among the inclusive‐teaching techniques that can be implemented during remote instruction are Scientist Spotlights—role‐model interventions that use available online materials to highlight the work of scientists representing multiple axes of diversity. We report here on the implementation of Scientist Spotlights in two courses, both of which emphasize ecology and evolution. We conclude with sample resources and suggestions for adopters. Abstract : Among the inclusive‐teaching techniques that can be implemented during remote instruction are Scientist Spotlights—role‐model interventions that use available online materials to highlight the work of scientists representing multiple axes of diversity. We report here on the implementation of Scientist Spotlights in two courses, both of which emphasize ecology and evolution. We conclude with sample resources and suggestions for adopters.